Analisis Framing Terhadap Pemberitaan Kebijakan Surat Keputusan Bersama (SKB) 3 Menteri tentang Pemakaian Identitas Agama pada Seragam Sekolah di Media Online Kompas.com dan Republika.com - Devi Ambarsari; Amalia Rosyadi Putri (Institut Agama Islam Tribakti (IAIT) Kediri, 2021)
Online media is a means for various categories to appreciate an event or any aspect that is useful and can provide information for the public. As is the case, the online media Kompas.com and Republika.com distribute their news online, so that it is easier for readers to find the information they want. In online media, Kompas.com and Replubika.com reported the policy of the Joint Decree (SKB) of 3 Ministers under the pretext that it was an attempt to find common ground from various differences in society. With the SKB 3 Ministerial policy, it is intended that each religious community understands religious teachings substantively, and does not force them to be the same. So that the reason, in general, makes researchers feel interested in describing the function of research that is seen directly or indirectly with the Framing Analysis of the William A. Gamson model and using the political economy theory of Vincent Mosco's media. The method used in this research is descriptive qualitative, with data in the form of documents. Data collection using text analysis and online data browsing. The results of the study, which found an interesting fact that the online media Kompas.com builds a good image of the 3 Ministerial SKB Policy issued by the government. The online media Kompas.com emphasizes that this 3 Ministerial Decree was issued for the common good in responding to an existing problem. Meanwhile, Republika.com takes a broader view of the opinion of the top officials in responding to this Decree of 3 Ministers. So that Republika.com gives the impression of being critical of the emergence of this 3 Ministerial SKB rule.